HEMATOLOGICAL PARAMETERS IN CARDIOVASCULAR DISEASES - Begum, Sadiqua; Rumana, Nausheen; Devi, Revathi ML; KS, Sadananda; M, Bharathi (Pakistan Journal of Physiology, 2018)
Background: Cardiovascular diseases are one of the leading causes for morbidity and mortality worldwide. They are mainly caused by atherosclerosis and its complications. Limited literature is available on the role of various haematological parameters.Our objective was to study various haematological parameters like RBC count, Haemoglobin, Haematocrit, Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), RedCell Distribution Width (RDW) in patients with Coronary Artery Disease (CAD). Methods: This was a descriptive study carried out on patients with CAD admitted to Sri Jayadeva Institute of Cardiovascular Sciences and Research, KRHospital Campus, Mysore, India in the age range of 30–60 years. Patients with impaired renal or hepatic function, known congenital heart disease/valvular heart diseases, known case of anaemia or being treated for anaemia, prolonged drug intake, thyroid disorders were excluded from the study. Blood samples were collected in an EDTA vaccutainers and analysed in automated cell analysers. Results: About 26.7% of the patients were <40 years age, 31.7% between 41–50 years and 41.7% were in 51–60 year group; 28.3% were known patients of hypertension, while 43.3% had diabetes mellitus. Haemoglobin in 48.3% of the study population was within normal range, while 16.7% of them had low levels and 35% had higher levels. Eighty percent of them had normal RBC count, 15% had increased count and 5% had decreased count. Fifty percent subjects had normal PCV while 20% had increased and 30% had decreased values. There was increased RDW-SD and RDW-CV in 66.7% and 50% of the study population respectively. Conclusion: There is role of various parameters like haemoglobin, MCV, RDW in pathogenesis of CAD. Alterations in various haematological parameters over a long run may be one of the various other reasons for the development of CAD. Regular health check-ups with precautionary measures taken in advance may reduce the prevalence of the disease. Pak J Physiol 2018;14(1):23–6